Argan Oil Exerts an Antiatherogenic Effect by Improving Lipids and Susceptibility of LDL to Oxidation in Type 2 Diabetes Patients - M. M. Ould Mohamedou; K. Zouirech; M. El Messal; M. S. El Kebbaj; A. Chraibi; A. Adlouni (International Journal of Endocrinology)
In this study, we investigate the effect of argan oil consumption on serum lipids, apolipoproteins (AI and B), CRP, and LDL susceptibility to oxidation in type 2 diabetic patients which are known to have a high level of cardiovascular risk due to lipid abnormalities and lipid peroxidation. For that, 86 type 2 diabetic patients with dyslipidemia were randomized to one group consuming 25 mL/day of argan oil during 3 weeks and control group consuming 20 g/day of butter in breakfast. After argan oil intervention, serum triglycerides decreased by 11.84%, (P=0.001), total chol by 9.13%, (P=0.01), and LDL-chol by 11.81%, (P=0.02). However, HDL-chol and Apo AI increased (10.51%, P=0.01 and 9.40%,  P=0.045, resp.). Susceptibility of LDL to lipid peroxidation was significantly reduced by increasing of 20.95%, (P=0.038) in lag phase after argan oil consumption. In conclusion, we show for the first time that consumption of argan oil may have an antiatherogenic effect by improving lipids, and the susceptibility of LDL to oxidation in type 2 diabetes patients with dyslipidemia, and can therefore be recommended in the nutritional management of type 2 diabetes.